2014
DOI: 10.1186/s13561-014-0033-3
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of prenatal care and birth weight in Kenya

Abstract: The paper investigates the effect of adequate use of prenatal care on birth weight in Kenya using data from the Kenya Demographic and Health Survey of 2008–2009 together with additional administrative data. Both a single–level model and a multi–level model are estimated. The estimation strategy controls for potential sample selection bias, potential endogeneity of prenatal care, and potential unobserved heterogeneity. The results indicate that adequate use of prenatal care increases birth weight, holding other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
17
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 36 publications
(62 reference statements)
3
17
0
1
Order By: Relevance
“…In the data selection step, a total of 10 attributes were selected, assuming to have a frequent pattern with ANC utilization based on the review from the previous literature dimensions in which ANC utilization was affected [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The dependent variable of this study is ANC utilization ("Yes" if the mother receives ANC for at least one time during a pregnancy, or else "No").…”
Section: Data Selection and Cleaningmentioning
confidence: 99%
See 1 more Smart Citation
“…In the data selection step, a total of 10 attributes were selected, assuming to have a frequent pattern with ANC utilization based on the review from the previous literature dimensions in which ANC utilization was affected [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27]. The dependent variable of this study is ANC utilization ("Yes" if the mother receives ANC for at least one time during a pregnancy, or else "No").…”
Section: Data Selection and Cleaningmentioning
confidence: 99%
“…Mother's age [12][13][14][15], place of residence [16][17][18][19], women's education [17,[20][21][22], husband education [19,21], women empowerment [23], women's occupation [24], economic status [13,22,25], parity [18,24], history of pregnancy complication [18,21], and media exposure [26,27]. Even though these factors are from different studies, my study has included and attested all the variables.…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in various contexts have confirmed the positive relationship between the quantity of prenatal care received and the birth weight of children (Awiti, 2014). Antenatal visits are also found to be associated with increased uptake of facility-based delivery and improved perinatal survival (Brown et al, 2008), which helps reduce several health risks for mothers and the newborns, as discussed above.…”
Section: The Need For Inclusive Healthmentioning
confidence: 81%
“…The importance of prenatal care in the production of infant health has been highlighted in a few studies conducted in developing countries (Awiti, 2014;Gajate-Garrido, 2013;Jewell & Triunfo, 2006;Gonzalez & Kumar, 2018;Nazim & Fan, 2011;Wehby, Murray, Castilla, Lopez Camelo, & Ohsfeldt, 2009). The importance of prenatal care in the production of infant health has been highlighted in a few studies conducted in developing countries (Awiti, 2014;Gajate-Garrido, 2013;Jewell & Triunfo, 2006;Gonzalez & Kumar, 2018;Nazim & Fan, 2011;Wehby, Murray, Castilla, Lopez Camelo, & Ohsfeldt, 2009).…”
Section: Previous Literaturementioning
confidence: 99%
“…There is a limited body of research that examines the effects of prenatal care on infant health in developing countries. The importance of prenatal care in the production of infant health has been highlighted in a few studies conducted in developing countries (Awiti, 2014;Gajate-Garrido, 2013;Jewell & Triunfo, 2006;Gonzalez & Kumar, 2018;Nazim & Fan, 2011;Wehby, Murray, Castilla, Lopez Camelo, & Ohsfeldt, 2009). Wehby et al (2009) reported an increase in birth weight of about 35 g per visit and a decrease of 30 g in birth weight due to per week delay in initiation of care in Argentina.…”
Section: Previous Literaturementioning
confidence: 99%